Predict the Level of Physical Performance in Terms of Some Functional Indicators for Basketball Players - Waleed Adnan Khafeef (Journal of Global Pharma Technology, 2018)
The science of sports training is a science that has been interested in the field of physical education in addition to other sciences in terms of field applications, which seeks to improve the levels of sports in various skills and activities, as access to high levels of sports and win will not be an easy process because the level of sports in Most of the activities have reached high levels in terms of technology and tactics. Among these games are the basketball game, which has witnessed a remarkable development in most countries of the world. In recent years, there has been an increasing interest in researching and exploring new methods of training players. As well as relying on the scientific basis of the determinants of the selection process of players who have the preparations and capabilities to enable them to play the game of basketball and predict their levels in the future. The researchers used the descriptive method in the method of associative and predictive relationships to suit the nature of the problem on the players of the basketball club Solidarity for the season (2018) of the (15) players. After testing the research sample and emptying the data in tables, the statistical process was carried out to reach the results through which the most important conclusions were reachedThe explosive power of the arms has a direct effect on the functional variables because the presence of explosive power is the result and indicator of the presence of adaptation in the functional variables that helped the player to produce high explosive power.Transient velocity is important in the success of movements and skills to a large degree where the transition speed is also the product of adapting functional variables at performanceKeywords: Prediction, Physical Performance, Functional Indicators and Basketball.